SISTEM INFORMASI JASA PERCETAKAN BERBASIS WEB MOBILE - HAYCAL, MUHAMAD VIVALDY HAYCAL PERDANA; Muhamad Vivaldy Haycal Perdana; Teguh Kristanto (STEKOM PRESS, 2023)
The development of print media is now more advanced, starting from ordering wedding invitations, business cards, letterheads, etc. offline, now it can be ordered online via the web. Currently, increasingly advanced technology, CV. Sinar Karya still uses the manual method to receive orders via telephone/walk in store. In the type of ordering goods, it is known that the customer generally has to come to the place to order the goods needed. But many customers feel dissatisfied with the system, technological developments are currently growing rapidly, namely making web orders that are easy for customers to understand. With advances in technology in Indonesia, the development of the e-commerce industry has made it easier for people to order goods online. This application was made using the waterfall method and built using the PHP programming language, BOOSTRAP. In developing this system through several stages, namely: needs analysis, system design, implementation, testing and development of the system. For the testing phase, a functional test is carried out using the Visual Studio application, used to test the function of the application that has been built, whether it meets what is needed. If the results of application testing have gone well and there are no problems. This web-based printing service system was created to make it easier for customers and owners to place orders and transactions. After the application is made and implemented, it can be concluded that in terms of customers, it is easier to place orders and make payment transactions at CV printing services. Sinar Karya. For owners it's easier when they want to see order data and customer data that has been registered in the application. Keywords: PHP, Ordering, Printing services, waterfall, boostrap